Segmentation of the Active Fault on the Cirebon-Semarang Segments as Revealed by DEM-Derived Geomorphic Indices - Jannah, Miftahul; Pamumpuni, Astyka; Sadisun, Imam Achmad (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This research focuses on the segmentation and tectonic activity of the Baribis-Kendeng Fault across the Cirebon to Semarang segments, revealed through the analysis of geomorphic indices derived from Digital Elevation Models (DEM). Utilizing geomorphic indices such as the Hypsometric Integral (HI), Stream Length-Gradient Index (SL), and SL/K ratio, the analysis was conducted on 33 streams crossing ten segments. The results indicate that the landscape in the research area is predominantly in the youthful stage, with HI values ranging from 0.459 to 0.492, indicating active tectonic uplift. Segments such as Ungaran and Pemalang exhibit significant tectonic activity, with high SL/K values, particularly in the Ungaran segment, where the SL/K value reaches 344.872. These findings suggest that fault activity in the region is ongoing, with stronger uplift patterns observed at the western and eastern ends of the fault, while relatively lower activity is found in the central area. This research highlights the ongoin tectonic processes shaping the region’s geomorphology and contributes to a better understanding of the active fault system in Java Island.